2012
DOI: 10.1103/physreve.86.022601
|View full text |Cite
|
Sign up to set email alerts
|

Electric-double-layer structure close to the three-phase contact line in an electrolyte wetting a solid substrate

Abstract: The electric-double-layer structure in an electrolyte close to a solid substrate near the three-phase contact line is approximated by considering the linearized Poisson-Boltzmann equation in a wedge geometry. The mathematical approach complements the semianalytical solutions reported in the literature by providing easily available characteristic information on the double-layer structure. In particular, the model contains a length scale that quantifies the distance from the fluid-fluid interface over which this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…As shown in Ref. [79], the EDL in the vicinity of such a wedge-shaped TPCL would be nontrivially different from the one-dimensional EDL distribution, and would substantially alter the present calculations. More importantly, the electroosmotic flow field in such a geometry remains unknown, particularly given the large singularity associated with the stress for r → 0 at the TPCL.…”
Section: Neglect Of the Charge Accumulation At The Air-liquid Interfacementioning
confidence: 77%
See 2 more Smart Citations
“…As shown in Ref. [79], the EDL in the vicinity of such a wedge-shaped TPCL would be nontrivially different from the one-dimensional EDL distribution, and would substantially alter the present calculations. More importantly, the electroosmotic flow field in such a geometry remains unknown, particularly given the large singularity associated with the stress for r → 0 at the TPCL.…”
Section: Neglect Of the Charge Accumulation At The Air-liquid Interfacementioning
confidence: 77%
“…This is the charge contained in the liquid volume (at the air-liquid interface) resulting from consideration of the wedge geometry at the three-phase contact line, especially relevant for thick EDLs and 0 < θ < π/2. This charge, therefore, is the charge of the EDL in a wedgelike volume [79,92], and is different from the charge that accumulates at the meniscus on account of the axial separation of charges (responsible for triggering the streaming potential). We have neglected this charge in the present analysis.…”
Section: Acknowledgmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The zeroth-order problem is thus identical to the one treated by Dörr & Hardt [30], allowing to use the model equation φ (0) (r, θ) = π/(2θ) exp(−cη) which contains the function c = c(θ). Improving upon the empirical expression for c provided by Dörr & Hardt [30], we present an analytical formula below. By means of the known potential φ (0) , the exponential first-order shape can be found from Eq.…”
Section: A Electrostatic Potential and Interfacial Shapementioning
confidence: 99%
“…The interface in electrocapillarity is not perfectly flat since the electric field on the interface is not uniform along the interface, which will be discussed later in this section. A couple of studies showed that the interface deformation can be significant and might induce capillary filling in a nanochannel [57][58][59]. However, we limit our attention only to the flat interface in order to treat the problem analytically as we did in our previous work [11].…”
Section: A Steric Effects On the Electrocapillarity Under The Constamentioning
confidence: 99%